2014
DOI: 10.5993/ajhb.38.6.17
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use of Lesbian, Gay, Bisexual and Heterosexual College Students

Abstract: ATOD use among LGB students was more prevalent than heterosexuals during the past 30 days, year, and life-time. LGB students report more negative alcohol consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
52
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 31 publications
7
52
1
Order By: Relevance
“…However, the findings concerning sexual-orientation drinking disparities among college students are inconsistent (Eisenberg and Wechsler, 2003; Hatzenbuehler et al, 2008; Kerr et al, 2014; McCabe et al, 2003, 2005; Reed et al, 2010; Ridner et al, 2006; Schauer et al, 2013; Talley et al, 2010, 2012). We know even less about whether LGB and heterosexual students drink in similar or different contexts (e.g., bars, Greek parties, off-campus parties).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the findings concerning sexual-orientation drinking disparities among college students are inconsistent (Eisenberg and Wechsler, 2003; Hatzenbuehler et al, 2008; Kerr et al, 2014; McCabe et al, 2003, 2005; Reed et al, 2010; Ridner et al, 2006; Schauer et al, 2013; Talley et al, 2010, 2012). We know even less about whether LGB and heterosexual students drink in similar or different contexts (e.g., bars, Greek parties, off-campus parties).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, sexual-orientation differences often vary by gender, with larger differences found among sexual-minority women compared to heterosexual women than differences among sexual-minority men compared to heterosexual men (Eisenberg and Wechsler, 2003; Hatzenbuehler et al, 2008; Kerr et al, 2014; McCabe et al, 2003, 2005; Ridner et al, 2006; Schauer et al, 2013; Talley et al, 2012). Specifically, several studies have shown that lesbians have a higher prevalence of alcohol use and are more likely to engage in heavy episodic use than heterosexual females (Ridner et al, 2006; Schauer et al, 2013; Talley et al, 2010), and there is some evidence that bisexual and “mostly heterosexual” females are also at substantially elevated risk (Eisenberg and Wechsler, 2003; Kerr et al, 2014; McCabe et al, 2005; Talley et al, 2010, 2012). Contrastingly, other studies have reported no differences in alcohol consumption by sexual orientation among female college students (Hatzenbuehler et al, 2008; McCabe et al, 2003; Reed et al, 2010; Talley et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the purpose of this study was to evaluate the degree to which a sample of LGB college students engages in HED, to identify commonly experienced alcohol-related negative consequences among LGB students, and to examine the degree to which PBS use moderates the relationship between alcohol consumption and alcohol-related negative consequences among LGB college students. LGB students have been observed to engage in HED at higher frequencies than those found among samples from the general college population (Kerr et al, 2014;Reed et al, 2010;Woodford et al, 2012); thus, we hypothesized that LGB students would engage in HED at a higher percentage than previously observed samples of college students. PBS usage has been observed to have an inverse relationship with consumption and alcohol-related negative consequences (Araas & Adams, 2008;Martens et al, 2004;Martens et al, 2007), and there is an absence of literature to indicate that LGB students will utilize PBS differently than their heterosexual peers.…”
mentioning
confidence: 84%
“…Furthermore, 19% of American college students in a national survey met criteria for alcohol abuse or dependence based on the Diagnostic and Statistical Manual of Mental Disorders, 4th edition, text revision (DSM-IV-TR) (NIAAA, 2013). Approximately 60-85% of LGB college students report past-month alcohol use in three studies (Kerr, Ding, & Chaya, 2014;Reed, Prado, Matsumoto, & Amaro, 2010;Woodford, Krentzman, & Gattis, 2012), and when studied in explicit comparison to heterosexual peers LGB students are more likely to report alcohol consumption (Kerr et al, 2014;Woodford et al, 2012), HED (Reed et al, 2010), and problematic drinking as measured by the CAGE questionnaire (Woodford et al, 2012). With more frequent reports of alcohol consumption and HED than the general college population, LGB college students appear to be an at-risk group for experiencing alcohol-related negative consequences, as increased alcohol consumption is related to more frequent-and more severe-alcohol-related negative consequences (Hingson et al, 2009).…”
mentioning
confidence: 99%